Changing gender roles in agriculture? Evidence from 20 years of data in Ghana - Lambrecht, Isabel B.; Schuster, Monica; Asare Samwini, Sarah; Pelleriaux, Laura (Wiley, 2018)
Many stylized facts about women in agriculture have been repeated for decades. Did nothing really change? Is some of this conventional wisdom simply maintained over time, or has it always been inaccurate? We use four rounds of cross‐sectional data from Ghana to assess some of the facts and to evaluate whether gender patterns have changed over time. We focus on five main themes: land, cropping patterns, market participation, agricultural inputs, and employment. We add to the literature by showing new facts and evidence for more than 20 years. Results show that stylized facts do not always hold, and that some of these “facts” change over time. We find significant variation in the extent of (changes in) gender discrepancies across themes, different agro‐ecological zones, ethnicities, household types, and women's role in the household.